Asian aquarium fishes in a Neotropical biodiversity hotspot: impeding establishment, spread and impacts - Magalhães, André L. B.; Jacobi, Claudia M. (Biological invasions, 2013)
We provide evidence of reproductive activities of nine Asian freshwater fish species belonging to three families in Atlantic Forest creeks located in the Paraíba do Sul River basin, southeastern Brazil, an area rich in endemic and endangered fish fauna. These non-native fishes were introduced into the natural systems by both accidental and intentional releases from ornamental fish farms in the region. Adults of all species were found reproducing during virtually all year round and showed fractionated spawning. Imature individuals (young-of-the-year and juveniles) were also frequent in the five sites. Most of the total sex ratios were close to 1:1. The frequent releases, warm water temperature, marginal vegetation providing food, protection and spawning sites, and the low richness of native fishes in these creeks can facilitate the establishment process of all species. The creeks can also act as dispersing agents of non-native fishes after flash floods, leading to biotic homogenization or differentiation in the local fish community, competition with native fishes, and parasite dissemination. Given the flourishing aquaculture activity in the area, it is expected that these and other non-native species cause extensive modifications in the regional ichthyofauna.